2014 IEEE International Conference on Image Processing (ICIP) 2014
DOI: 10.1109/icip.2014.7025695
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight mobile object recognition

Abstract: The purpose of our demo is to show the application and performance of some low-complexity image descriptors in object recognition under realistic circumstances. We built a client-server system where several image retrieval methods and image segmentation approaches can be tested with the help of a network connected Android device (mobile phone, table or head mounted computer). A modified version of the CEDD (Color and Edge Directivity Descriptor) is proposed, as the most robust lightweight descriptor found in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Our recognition system has higher values for all of the hardware parameters, but it has three main benefits: (i) performing the recognition process in two stages, which reduces the possibility of passing and accepting infected biometric data; (ii) performing a filtering process to eliminate the impact of a Hardware Trojan if applicable; and (iii) easier to locate an intrusion in the system due to a decussate and chaining hardware-software architecture. Meanwhile, our system has a conspicuously smaller hardware footprint in comparison to the existing exclusively hardware-based works, and its algorithm is computationally much simpler in comparison to the existing lightweight biometric recognition systems [12][13][14][15][16][17][18][19][20][21][22]. …”
Section: Resultsmentioning
confidence: 99%
“…Our recognition system has higher values for all of the hardware parameters, but it has three main benefits: (i) performing the recognition process in two stages, which reduces the possibility of passing and accepting infected biometric data; (ii) performing a filtering process to eliminate the impact of a Hardware Trojan if applicable; and (iii) easier to locate an intrusion in the system due to a decussate and chaining hardware-software architecture. Meanwhile, our system has a conspicuously smaller hardware footprint in comparison to the existing exclusively hardware-based works, and its algorithm is computationally much simpler in comparison to the existing lightweight biometric recognition systems [12][13][14][15][16][17][18][19][20][21][22]. …”
Section: Resultsmentioning
confidence: 99%
“…In [ 25 ], it is shown that the color and edge directivity descriptor (CEDD) [ 26 ] is a robust visual tool and can be computed quickly in mobile platforms. The CEDD is an area-based descriptor where pixels are classified into one of six texture classes (non-edge, vertical, horizontal, 45 and 135 degree diagonal, and non-directional edges) with the help of the MPEG-7 Edge Histogram Descriptor.…”
Section: Viewer-centered Visual Representation With Orientation Damentioning
confidence: 99%